(untitled) (Journal of the College of Basic Education, 2025)
The level of sound pollution, which is a prominent feature of the environment, varies depending on its source. It affects objects and buildings in its surroundings in varying proportions. As a whole, schools, like other buildings, are vulnerable to sound pollution. Since there are a number of schools near the main streets and commercial and industrial activities, so these buildings are very sensitive to environmental noise (due to the work they provide to students of science, which requires rest and tranquility) in many cases exposed to high levels of noise. The adeometer was used to measure the noise level in the selected locations. Where noise level measurements were made on the basis of 14 days and during (3 days a week) (Sunday, Tuesday and Thursday) and the work was divided into two weeks, and the work was distributed over several times (morning, evening period).